Identitas Orang Bugis di Dabong, Kalimantan Barat - Saripaini Saripaini; Yusriadi Yusriadi (Khatulistiwa, 2016)
This paper discusses the Bugis people in West Kalimantan. The author seeks to see what sets the identity of the Bugis apart from the Malays, and what basis that can be used to identify their characteristics. The data were collected in Dabong village, a remote village in Kubu Sudistrict of Kubu Raya Regency, West Kalimantan, which takes 7 hours by public transport from Pontianak. The data were collected through field observations on people's lives as well as interviews with community leaders and some residents of Bugis descent. The interviews obtained information that the Bugis people had settled in Dabong for 6 generations and mingled with the local community. The Bugis descendants in Dabong have now become Malay. They introduce themselves with the Malay identity, and known as Malay to outsiders as well. The option to become Malay was made as a pragmatic consideration that in the village, the Malay society and culture was dominant. However, despite their Malay identity, the Bugis remain recognizable in terms of identity, which is reflected through cultural activities. Some Malay customs that they practice still exhibit obscure Bugis characteristics. The choice to preserve the traits of Bugis among people of Bugis descent is not because of ethnic consciousness, but rather due to cultural awareness, the awareness of their obligations to implement what has been practiced by their ancestors, and the belief that every ritual performed has consequences.